Implant stability in the treatment of MRSA bone implant infections with linezolid versus vancomycin in a rabbit model - Schröder, Kerstin; Lorenz, Helga; Swoboda, Stefanie; Helbig, Lars (Journal of orthopaedic research, 2012)
Abstract The increasing prevalence of methicillin?resistant Staphylococcus aureus (MRSA) infections represents a significant healthcare burden. Vancomycin and linezolid exhibit potent clinical and microbiological activity in MRSA infections. Our purpose was to investigate the efficacy of linezolid versus vancomycin in experimental implant infections and the influence on implant stability in a rabbit model. Thirty?six female New Zealand White rabbits received surgical insertion of titanium implants into their distal femurs and were randomly assigned to six groups (A: infected, no treatment; B: infected, vancomycin; C: infected, linezolid; D: no infection, no treatment; E/F: no infection, vancomycin or linezolid, respectively). Antibiotics were administered, and plasma levels determined. Bone?implant specimens were tested for mechanical stability of fixation. Quantitative histomorphometry of bone and soft tissue was performed using computerized image analysis. Plasma levels of linezolid and vancomycin were within the respective therapeutic ranges. Microbiological analysis of specimens from infected rabbits showed MRSA tissue colonization in all untreated animals, in two of six vancomycin?treated animals, and in none of the linezolid?treated animals. Antibiotic treatment improved mechanical stability significantly (p?=?0.004) with both vancomycin and linezolid. Mechanical testing correlated with histomorphometry results. A significant negative correlation was found between displacement of the implant and the percentage of calcified tissue around the implant, and a significant positive correlation was found between displacement of the implant and the amount of noncalcified tissue. Our data indicate that both treatment regimens improved implant stability. ? 2011 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 30:190-195, 2012
Published online: 3 August 2011
Gesehen am 06.04.2018